আমার কর্ম আমার জীবন - এরশাদ, হুসেইন মুহম্মদ ১৯৩০-২০১৯. (ঢাকা : আকাশ, 2016)
Autobiography of Hussain Muhammad Ershad, b. 1930, politician and former president of Bangladesh.
Donated by Akbar Ali Khan
In Bengali; includes passages in English.
Keywords: Ershad, Hussain Muhammad, -- 1930-2019.; Politicians -- Bangladesh -- Biography; Presidents -- Bangladesh -- Biography; Bangladesh -- Biography; Bangladesh -- Politics and government -- 1971-